Spatial Differences and Influencing Factors of Energy Poverty: Evidence From Provinces in China - Jia, Wenxing; Wu, Shengnan (Frontiers in Environmental Science, 2022)
The complex and serious energy poverty problem has seriously affected the residents' health and quality of life and posed a great challenge to the country's macroeconomic development. This paper analyzes the spatial distribution of energy poverty and the characteristics of inter-regional differences among 30 provinces in mainland China from 2008 to 2019 by constructing an evaluation index system of energy poverty. It empirically examines the main causes of inter-regional disparities in energy poverty based on a "relational data" perspective. We also empirically examined the main reasons for the disparity between energy poverty regions based on "relational data." The results show that the spatial distribution of energy poverty in China shows the characteristics of "high in the west and central part and low in the east," and the spatial pattern is relatively stable. From the perspective of the time dimension, the overall problem of energy poverty in China has been alleviated during the sample period, and the overall gap in energy poverty has shown a decreasing trend. The difference in energy poverty between regions is the main source of the overall gap, but its contribution rate is also gradually decreasing. The results of empirical analysis show that reducing the imbalance of industrial structure, energy price, and energy investment level among regions can effectively reduce the inter-regional energy poverty gap. In addition, there are differences in the dominant factors that determine the difference in energy poverty within the East and West regions. In this regard, it is recommended to further improve the relevant policies in developing new energy sources according to local conditions, reasonably increasing energy construction investment, strengthening technological innovation, establishing financial guarantee mechanisms, and guiding residents to consume modern living energy.